Laulāto mantiskās attiecības Latvijā no 19.gs. vidus līdz mūsdienām - Ciematniece, Ilze (Latvijas Universitāte, 2007)
1993.gadā, atjaunojot 1937.gada Civillikumu notika tā gramatiska pielāgošana mūsdienu situācijai, neizvērtējot šo tiesību normu saturu vēsturiskā aspektā, kas ir radījis virkni tiesību normu piemērošanas problēmu un neskaidrības laulāto mantiskajās attiecībās. Diplomdarba pirmajā nodaļā tiek apskatīta ģimenes tiesību attīstība Latvijas teritorijā līdz 19.gs vidum, apskatot svarīgākos ģimenes tiesību avotus. Vēsturiskā apskata rezultātā tiek secināts, ka līdz 19.gs. vidum Latvijas teritorijā laulāto mantiskās attiecības reglamentē dažādi avoti, bet tiem ir kopīga iezīme - laulāto mantiskajās attiecībās pastāv vīra aizbildnības princips pār sievu. Otrajā nodaļā tiek apskatītas laulāto mantisko attiecību vēsturiskā attīstība Latvijā sākot no 1864.gada līdz 1940.gadam, pievēršoties G.E.Bunges sastādītajai Baltijas Vietējo Likumu kopojuma III daļai (BVLK) un tālāk apskatot 1937.gada 28.janvārī pieņemto Latvijas Republikas Civillikumu. Nodaļā tiek analizētas BVLK III daļā noteiktās laulāto mantisko attiecību sistēmas, to atšķirības no 1937.gada 28.janvārī pieņemtā Civillikumā pastāvējušām laulāto mantisko attiecību sistēmām, apskatot dažādu laulāto mantisko attiecību institūtu vēsturisko attīstību un būtiskākās iezīmes. Analizējot minētos likumus tiek izdarīts secinājums, ka 1937.gada Civillikumā likumiskā laulāto mantisko attiecību sistēma ir pārņemta no Kurzemes zemes un pilsētu tiesībām, kas paredzēja laulāto mantas šķirtību ar vīra pārvaldīšanas un lietošanas tiesībām pār sievas mantu, kā līgumiskās laulāto mantisko attiecību sistēmas nosakot visas mantas šķirtības sistēmu, kas bija spēkā Latgalē un laulāto mantas kopības sistēmu, kas bija spēkā Vidzemes pilsētu tiesībās. Trešajā nodaļā tiek apskatīta Latvijas Republikas Civillikuma spēkā esošā redakcija. Nodaļa veltīta problēmu apzināšanai un analīzei laulāto likumiskajās mantiskajās attiecībās, nonākot pie secinājumiem, ka pārstrādājot Civillikuma Ģimenes tiesību nodaļas normas, ir mainījies atsevišķās mantas institūta saturs laulāto likumisko mantisko attiecību sistēmā, kā arī ir tikusi izslēgta laulātā „atsevišķi iegūtā manta”, kas bija ietverta 1937.gada Civillikumā un kuras neesamība likumā rada likuma piemērošanas problēmas, nosakot laulātā mantas piederību.

In 1993, when reenacting the Civil Law enforced in 1937, it was grammatically adjusted to the present day situation, not evaluating the contents of these Civil Law norms in their historical aspect, thus creating a train of problems in applying several of these norms as well as obscurity within the spouses’ property relations. The first chapter of this diploma work deals with the historical evolution of the family rights in the territory of Latvia until the middle of the 19th century, concentrating on the most significant sources of the family rights. The historical overview draws the conclusion that the spouses’ property relations in the territory of Latvia have been regulated by several different sources until the mid 19th century, still having the same trait – common principle of husband’s patronage over his wife within their property relations. The second chapter concentrates on the historical development of the spouses’ property relations in Latvian territory from the 1864 till 1940, dealing with the III part of the Local Digest of the Civil Laws compiled by G. E. Bunge and analysing the Latvian Civil Law, enforced in January 28, 1937. Hereby the systems of the spouses’ property relations established by the Local Digest of the Civil Laws are analysed and the differences between those and the ones established by the Latvian Civil Law, enforced in January 28, 1937, thus examining the historical development of several institutions concerning the spouses’ property relations and their most essential features. Considering the above mentioned Laws leads to a conclusion that the system of the spouses’ property relations established by the Civil Law of the 1937 has been adopted from the Local Digest of the Civil Laws, and exactly from the Kurland land and town laws, which provided the partition of the spouses’ property with husband holding the rights of management and usage over his wife’s property; while setting the systems of the contractual property relations of the spouses by establishing the partition of all of the spouses’ property, that was in force in Latgale and the system of common property of the spouses that was established by the Local Digest of the Civil Laws, Vidzeme town laws. The third chapter is devoted to the presently effective draft of the Latvia’s Civil Law. Within this chapter problems of the legally set spouses’ property relations are defined and analysed, coming to a conclusion, that by revising the norms of the Family rights chapter of the Civil Law, the institute of the segregated property has changed it’s content within the system of the legal property relations of the spouses, as well as the institute of the “separately acquired property of a spouse” has been excluded, though it was effective within the Civil Law of the 1937, and the absence of it causes problems when applying the law to identify the spouses’ property.
Property relations of maritals in Latvia from the middle of 19th century to nowadays
Keywords: Tiesības